VISUAL ARTS OF SUKATANI BAND ON SOCIAL MEDIA AS PARTICIPATORY MOVEMENT AFFECTS THE GOVERNMENT POLICIES - Sari Wulandari; Elmi Novita (jfpublisher, 2025)
This research examines the Sukatani Band case and their controversial song